ANALISIS MANAJEMEN RISIKO WAKAF UANG DENGAN METODE ERM COSO - Vita Sarasi; Joval Ifghaniyafi Farras; Jasmine Hanjani Putri (Jurnal Ilmiah Ekonomi Islam, 2022)
Cash waqf management is different from other Islamic philanthropic asset management, because nazhir as waqf manager must maintain the endowment of waqf and also develop waqf assets so that the benefits can be distributed to mauquf'alaih. This study aims to analyze risk management, find out the risks contained in the management of cash waqf as well as to know the risk control carried out by the Al-Azhar Waqf Institution, Jakarta. The approach used in this research is Enterprise Risk Management (ERM) COSO 2004 (Godfrey, 1996). The results of this study found that there are 31 risks in cash waqf management in Al-Azhar, namely 10 risks in collecting cash waqf funds, 13 risks in managing cash waqf funds and 8 risks in the distribution of cash waqf proceeds that need to be mitigated or transferred in collaboration with other institutions so that the risk is not fully borne alone.